MENENTUKAN STANDAR JUMLAH WAREHOUSEMAN DI GUDANG SPARE PARTS ALAT BERAT MENGGUNAKAN PENDEKATAN FULL TIME EQUIVALENT (FTE) - Abimanyu; Ramadhanti, Lifia Citra (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
This research establishes a standard for determining the optimal number of warehousemen in heavy equipment spare parts warehouses using the Full-Time Equivalent (FTE) method. PT XYZ, a leading dealer in Indonesia, operates 63 warehouses with 624 warehousemen but lacks a clear workforce standard. The study uses a quantitative, descriptive approach, analyzing operational data from a Jakarta warehouse. Activities and processing times were measured to calculate FTE based on average monthly line items and effective working hours. Results show that nine core activities require 14 warehousemen for optimal efficiency. Implementing this standard can reduce operational costs, balance workloads, and improve customer satisfaction. The findings provide practical and academic contributions to human resource management in logistics and offer a replicable model for similar industries.